Financial Levers of State Support for Rural Development: European Experience and Domestic Realities - Abramova Iryna V. (PH "INZHEK", 2021)
The article is aimed at substantiating financial levers of state support for rural development from a theoretical and methodological viewpoint, taking into account European and domestic experience, and at developing practical recommendations for their perfecting. The study has been carried out according to the general methodological scheme of the systemic approach using the following methods: statistical and economic, computational and structural, abstract-logical, comparative and analytical, etc. The European experience of providing state support for rural development is analyzed, and ways to adapt it to the Ukrainian reality are outlined. Taking into consideration the cost structure in the joint budget of the European Union, it is clear that the EU member states pay special attention to solving economic, environmental and social issues in the context of sustainable rural development. It is determined that rural communities in Ukraine are in extremely difficult conditions, as unemployment and poverty remain widespread; the level of social, medical, educational, and cultural services provided for the rural population remains low; the infrastructural development of rural settlements is unsatisfactory. Emphasis is placed on the fact that financial support for agriculture and rural areas in Ukraine is focused mainly on their economic development. It is proved that sustainable rural development will be possible through naturally combining its economic, social and environmental components. It is determined that the key role in this process belongs to the state. It is argued that due to such levers of influence as budget financing, soft loans, tax and investment incentives, etc., the state can positively influence the diversification and development of entrepreneurship, increase jobs and employment in rural areas. Emphasis is placed on the necessity to form a social protection system, as well as cultural basis for rural development, provide support for and improvement of the environmental conditions in rural areas.